A comparative study in money attitude among university students: a gendered view - Falahati, Leila; Paim, Laily (Marsland Press, 2011)
The paper aims to examine gender differences in money attitude among college students. Using the stratified sampling method, 2,340 college students from six public and five private colleges were studied. The findings indicate gender differences for different dimensions of money attitude, in which males were attached to money as a power/prestige tool while experiencing anxiety and having a retentive attitude toward money. Meanwhile female students were conservatively minded about money, as well as being attached to money for self-gratification purposes.